2001
DOI: 10.4049/jimmunol.166.9.5407
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of TNF-α-Related Apoptosis-Inducing Ligand in the Enhanced Cytotoxicity of IFN-β-Stimulated Human Dendritic Cells to Tumor Cells

Abstract: TNF-α-related apoptosis-inducing ligand (TRAIL) is characterized by its preferential induction of apoptosis of tumor cells but not normal cells. Dendritic cells (DCs), besides their role as APCs, now have been demonstrated to exert cytotoxicity or cytostasis on some tumor cells. Here, we report that both human CD34+ stem cell-derived DCs (CD34DCs) and human CD14+ monocyte-derived DCs (MoDCs) express TRAIL and exhibit cytotoxicity to some types of tumor cells partially through TRAIL. Moderate expression of TRAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
2
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 48 publications
10
124
2
3
Order By: Relevance
“…Previous reports have demonstrated that human peripheral blood dendritic cells (PBDC) can express TRAIL and kill TRAIL-sensitive target cells, such as HL60, under certain circumstances. (7) To ascertain whether CBDC can kill tumor cells through TRAIL, HL60 was used as the target cell in our study. Based on the possible different sensitivity of variable tumor cells to cytotoxicity mediated by CBDC, the other hematopoietic tumor cells lines, including Jurkat and Daudi, were also used as target cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have demonstrated that human peripheral blood dendritic cells (PBDC) can express TRAIL and kill TRAIL-sensitive target cells, such as HL60, under certain circumstances. (7) To ascertain whether CBDC can kill tumor cells through TRAIL, HL60 was used as the target cell in our study. Based on the possible different sensitivity of variable tumor cells to cytotoxicity mediated by CBDC, the other hematopoietic tumor cells lines, including Jurkat and Daudi, were also used as target cells.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the reports that activated human PBDC were effective in killing tumor cells via involvement of an membranebound TNF family apoptosis-inducing pathway, (7,8) we measured cell surface and cytoplasmic expression of three major members of TNF family, including TRAIL, FasL and TNF-α, on CBDC before and after LPS or IFN-γ stimulation. As revealed in Figure 4, TRAIL, FasL and TNF-α were weakly expressed on the surface of CBDC, and could not be up-regulated by LPS or IFN-γ stimulation.…”
Section: Ifn-γ or Lps Stimulation Up-regulated Cytoplasmic Trail Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…69,70 Human blood cDCs acquire the ability to kill tumor cells via TRAIL expression or TNF-a secretion, upon IFN-a or IFN-g stimulation, 52,71 and monocyte-derived DCs upon IFN-b stimulation or measles virus infection. 72,73 Immature DCs have also been shown to kill freshly isolated tumors. [74][75][76] Although in vitro-derived immature DCs kill target cells very efficiently at low effector/target ratios via an apoptotic mechanism involving DNA fragmentation, mitochondrial dysfunction, and late membrane disruption, the level of cytotoxicity found in the freshly isolated, immature DCs remains low and questionable.…”
Section: Killer Dcsmentioning
confidence: 99%
“…[10][11][12][13] It has also been reported that activation of DCs with IFN-a or -b leads to upregulation of TNF-a-related apoptosis-inducing ligand (TRAIL) expression, and to direct tumoricidal activity mediated by DCs via TRAIL. 14,15 IFN-a-transduced tumor cells also activate and promote the survival of tumor-specific CD8 + CTLs in vivo. 16 Although the type I IFN protein has been used therapeutically for patients with malignant gliomas by systemic administration and its safety has been demonstrated, 17,18 it has been difficult to achieve effective cytokine levels within the tumor at clinically tolerated doses.…”
Section: Introductionmentioning
confidence: 99%